Journalism Ethics : 21 Essentials from Wars to Artificial Intelligence - Wishart, Eric (Hong Kong University Press, 2024)
This concise and authoritative work offers the latest guidance on journalism ethics for students and media professionals and will help empower news consumers to make informed decisions about the trustworthiness of their sources of information. It offers advice on all aspects of journalism ethics including accuracy and seeking the truth, representation of women, LGBTQ coverage, climate change, mental health, use of images, conflict reporting, elections, and how to use artificial intelligence. The author brings a unique perspective and depth of knowledge to the complex challenges facing journalists and news consumers in this era of fake news, disinformation, and artificial intelligence.